2011
DOI: 10.1177/0143034311402308
|View full text |Cite
|
Sign up to set email alerts
|

School bullying by one or more ways: Does it matter and how do students cope?

Abstract: Students (n ¼ 452; ages 12-14 years) attending two South Australian metropolitan high schools completed the 'Living & learning at school: Bullying at school' survey in which they reported ways they were bullied and the strategies they would use to deal with bullying. Results showed that a small proportion of students were bullied in three or more ways, and that males and females differed in the coping strategies they would use if bullied. Significant differences were found between bullied and not bullied stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 50 publications
9
66
1
7
Order By: Relevance
“…In relation to overall levels of bullying and victimisation, our results reveal a traditional pattern in which the most frequent forms of bullying and victimisation reported are verbal followed by indirect and physical. These results are consistent with a recent study conducted by one of us in the same city (Skrzypiec, Slee, Murray-Harvey, & Pereira, 2011). We found very low incidences of the more extreme behaviours including use of weapons and extortion.…”
Section: Discussionsupporting
confidence: 93%
“…In relation to overall levels of bullying and victimisation, our results reveal a traditional pattern in which the most frequent forms of bullying and victimisation reported are verbal followed by indirect and physical. These results are consistent with a recent study conducted by one of us in the same city (Skrzypiec, Slee, Murray-Harvey, & Pereira, 2011). We found very low incidences of the more extreme behaviours including use of weapons and extortion.…”
Section: Discussionsupporting
confidence: 93%
“…& Agatston, 2012; Olweus, 1993;Olweus & Limber, 2010a;Patchin & Hinduja, 2012;Skrzypiec, Slee, Murray-Harvey, & Pereira, 2011). Importantly, the source of the power imbalance could be any number of things including physical strength, status, and knowledge.…”
mentioning
confidence: 99%
“…In spite of their differences, involvement in the two types of bullying appears to be related (Hinduja & Patchin, 2008;Skrzypiec et al, 2011;Ybarra & Mitchell, 2004), with some researchers suggesting that cyberbullying is simply an extension of traditional bullying (Li, 2005(Li, , 2006. For example, Hinduja and Patchin (2010) found that 65% of victims of cyberbullying were also victims of traditional bullying; 77% of perpetrators of cyberbullying reported perpetrating traditional bullying.…”
mentioning
confidence: 99%
“…Así, los aspectos más amplios de los contextos de clase, escolar, familiar y comunitario igualmente precisan ser considerados como determinantes de interacciones sociales señaladas como violencia. En esta perspectiva, la implicación y unión de esfuerzos de toda la comunidad escolar, juntamente con las familias de los estudiantes, aseguran alteraciones positivas en los estándares de convivencia en la escuela, en el sentido de instituir una cultura de no violencia y transformar el ambiente escolar en un local seguro en la percepción de los estudiantes (28) .…”
Section: Nº 48 Octubre 2017unclassified